2013
DOI: 10.1166/jnn.2013.7781
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Antibacterial Activities of Silver Nanoparticles Against <I>Bacillus subtilis</I>

Abstract: Silver nanoparticles (AgNPs) with different sizes (5, 15 and 55 nm) were synthesized via simple method, and characterized by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), energy-dispersive X-ray microanalysis (EDX) and ultraviolet-visible absorption spectroscopy (UV-Vis). The antibacterial activities of the prepared AgNPs against Gram-negative Escherichia coli (E. coli), Gram-positive Staphylococcus aureus (S. aureus) and Bacillus subtilis (B. subtilis) were evaluated by inhibition zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 0 publications
1
60
0
Order By: Relevance
“…Another possibility could be the AgNP-induced leakage in the cell wall of bacteria, as suggested by Li et al (2013), who showed that well-characterized AgNP exhibited more sensitivity for Gram-positive bacteria compared to Gramnegative bacteria, when cultured separately or in a co-cultured condition. Another study also showed that both, Gram-positive Staphylococcus aureus and Gram-negative E. coli, were susceptible to the AgNP-doped silica particles (Bugla-Ploskonska et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility could be the AgNP-induced leakage in the cell wall of bacteria, as suggested by Li et al (2013), who showed that well-characterized AgNP exhibited more sensitivity for Gram-positive bacteria compared to Gramnegative bacteria, when cultured separately or in a co-cultured condition. Another study also showed that both, Gram-positive Staphylococcus aureus and Gram-negative E. coli, were susceptible to the AgNP-doped silica particles (Bugla-Ploskonska et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…28 Characterization Scanning electron microscopy (SEM) images and energy dispersive X-ray (EDX) spectra were obtained on a Hitachi S4800 scanning electron microscope operating at 5.0 kV. Ag/Bi 2 O 3 nanocomposites with different Ag quantities were synthesized by the deposition-precipitation method.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Li et al showed that the antibacterial activity of AgNPs decreased with increase of the nanoparticle size. 137 The highest antibacterial effect was observed in the case of smallest nanoparticles, 5 nm, in which attachment of the nanoparticles onto the cell membrane led to membrane damage, increased membrane permeability and nally cell death. To this end, Ivask et al tested toxic effect AgNPs with different sizes on various types of organisms and cells.…”
Section: Factors Affecting the Antimicrobial Activity Of Silver Nanopmentioning
confidence: 99%